2007
DOI: 10.1016/j.ejcts.2007.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Compared fate of small-diameter Contegras® and homografts in the pulmonary position

Abstract: In the first 4 years after pulmonary implantation of small-diameter Contegras and homografts, the fate of both conduits was statistically similar, in spite of different behavior. As Contegras is 'off-the-shelf' available, it constitutes a sound alternative to homograft for right ventricular outflow tract reconstruction in neonates and infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 7 publications
2
14
1
2
Order By: Relevance
“…This is nearly identical to that reported by Sinzobahlmvya and associates in a series of 76 PHs ranging in size from 8 mm to 13 mm [19]. The 5-and 10-year freedom from dysfunction in the BJV cohort was significantly better at 90% and 85%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…This is nearly identical to that reported by Sinzobahlmvya and associates in a series of 76 PHs ranging in size from 8 mm to 13 mm [19]. The 5-and 10-year freedom from dysfunction in the BJV cohort was significantly better at 90% and 85%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Contegra durability was lower, but the number of Contegras implanted is too small (n = 8) and the time of follow-up too short (maximum 29 months) to allow definitive conclusions. Nevertheless, results in this study were not as promising as recently reported by us [13] and by the aforementioned multi-institutional study [9]. It is to be noted that these two reports do not supply conduit survival beyond three postoperative years.…”
Section: Discussioncontrasting
confidence: 63%
“…The alternative to homograft implantation is represented by heterograft conduits. Despite that some case series using heterografts report good results on survival and freedom from re-intervention, [18][19][20] it is usually supported that heterografts have a higher rate of re-intervention compared to homografts [21]. Failure of heterografts is secondary to valve leaflet degeneration, sternal compression, intimal peel formation and calcification.…”
Section: Discussionmentioning
confidence: 88%